The design and development of an HIV-1 vaccine to elicit a broadly neutralising antibody response - Wan, L; Lai Kin Derek Wan (2012)
Despite 30 years of research, a prophylactic vaccine against HIV-1 is still lacking and is urgently needed in order to control the global AIDS pandemic. The discovery of broadly neutralising antibodies (BNAbs) was an important step for HIV-1 research but no vaccine candidate tested so far has been able to reproduce responses containing such antibodies, and it remains unclear how this could be achieved via immunisation. In this thesis, I attempted to explore this gap of knowledge in two ways. First, certain features (‘signatures’) of the Env protein that were associated with a broadly neutralising response were identified through machine learning. Further characterisation of these signatures revealed several ways by which these naturally-occurring mutations might alter the immunogenicity of the Env protein that could result in the elicitation of a broadly neutralising response. The incorporation of such signatures in future vaccine design could be useful as the Env protein might adopt a conformation that encourages the elicitation of a broadly neutralising response. Second, 3 novel vaccination approaches were proposed aiming to induce a BNAb antibody response. The development of 2 approaches proved to be difficult and was not continued. For the third approach, non-neutralising immunogen-derived antibodies were used to mask immunodominant epitopes on the Env protein (i.e. ‘antibody-shielding’), thus allowing the antibody response to be focused to the highly conserved CD4 binding site (CD4bs). Subsequent immunisation of the antibody-shielded gp120 proteins in mice and rabbits demonstrated that antibody-shielding was able to significantly dampen the V3-specific antibody response while retaining the CD4bs-specific response. However, the antibody response to the V1/V2 loop was enhanced upon V3-dampening which indicates that further optimisation of the antibody-shield is needed in order to eliminate any antibody response towards the immunodominant regions. In conclusion, these results are the first description of a number of novel vaccination ideas and provide valuable insights into how these approaches could be optimised to become effective HIV-1 vaccines that can lead to the elicitation of a broadly neutralising antibody response.